HUBUNGAN PEMANFAATAN SITUS GOOGLE DAN MOTIVASI BELAJAR DENGAN PRESTASI BELAJAR SOSIOLOGI SISWA KELAS XI SMAN 3 KLATEN TAHUN PELAJARAN 2012/2013 - Ningrum, Wulan (ISSN.2252-8407)
HUBUNGAN  PEMANFAATAN SITUS GOOGLE DAN MOTIVASI BELAJAR  DENGAN PRESTASI BELAJAR SOSIOLOGI SISWA KELAS XI SMAN 3 KLATEN TAHUN PELAJARAN 2012/2013Oleh : Wulan Ningrum   ABSTRACT Wulan Ningrum. THE RELATIONSHIP OF GOOGLE SITE UTILIZATION AND LEARNING MOTIVATION TO SOCIOLOGY LEARNING ACHIEVEMENT OF THE XI GRADERS OF SMAN 3 KLATEN IN THE SCHOOL YEAR OF 2012/2013. Thesis, Surakarta: Teacher Training and Education Faculty. Surakarta Sebelas Maret University, July 2013.This research aimed to find out: (1) whether or not there is a positive relationship between Google site utilization and sociology learning achievement of the XI graders of SMAN 3 Klaten in the school year of 2012/2013, (2) whether or not there is a positive relationship between learning motivation and sociology learning achievement of the XI graders of SMAN 3 Klaten, (3) whether or not there is a positive relationship of Google site utilization and learning motivation to sociology learning achievement of the XI graders of SMAN 3 Klaten.The method employed in this research was a descriptive quantitative one. The population of research was the XI IPS (Social Science) graders of SMA Negeri 3 Klaten in the school year of 2012/2013, consisting of 144 students. The proportion of sample was 20% of all population number existing with 20 students as instrument tryout sample and 29 students as the research sample. The sample was taken using stratified purposive random sampling. Techniques of collecting data employed were questionnaire, achievement test, documentation and observation. Technique of analyzing data employed was statistical analysis with multiple correlation coefficient technique.Considering the result of research, the following conclusions could be drawn: (1) Hypothesis 1 ?there is a significant relationship between Google site utilization and sociology learning achievement of the XI graders of SMAN 3 Klaten in the school year of 2012/2013? was supported. It could be seen from the result of data analysis showing rx1y = 0.608 and p = 0.001. (2) Hypothesis 2 ?there is a significant relationship between learning motivation and sociology learning achievement of the XI graders of SMAN 3 Klaten in the school year of 2012/2013? was supported. It could be seen from the result of data analysis showing Rx2y = 0.542 and p = 0.003. (3) Hypothesis 3 ?there is a significant relationship of Google site utilization and learning motivation to sociology learning achievement of the XI graders of SMAN 3 Klaten in the school year of 2012/2013? was stated as being supported. It could be seen from the result of data analysis showing R(x1, 2) = 0.617 and p = 0.001. Keywords: The utilization of Google site, Learning Motivation, Sociology Learning Achievement.